Utilization of National Health Insurance capitation funds at puskesmas: A qualitative study in Medan Labuhan Subdistrict, Medan City - Parulian, Alfred Padumpang; Nababan, Donal; Tarigan, Frida Lina; Wandra, Tony; Sitorus, Mido Ester J. (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
The Indonesian National Health Insurance (JKN) system uses a capitation payment mechanism to fund primary healthcare services. However, utilization of these funds has been a subject of concern because of the potential for unutilized funds and inefficient allocation. This study aimed to investigate the utilization of capitation funds in three Puskesmas (primary healthcare facilities) in Medan Labuhan, Medan City, in 2023. Using a qualitative descriptive research approach, data were collected through in-depth interviews, document analyses, and direct observations. The participants included puskesmas heads, technical implementation officers, primary healthcare service team leaders, financial subsection heads, and health office department heads. Triangulation was used to ensure data validity. The study revealed that overall capitation fund utilization was suboptimal, particularly in terms of operational cost support. This was attributed to delays in budget implementation documents, lengthy and bureaucratic procurement processes, and a lack of understanding among capitation fund management personnel at Puskesmas. To optimize capitation fund utilization, this study recommends streamlining bureaucratic procedures, providing training for capitation fund management personnel, and adopting effective financial management practices for public service agencies. These measures can contribute to improved quality and professionalism in healthcare services delivered by Puskesmas in Medan Labuhan.